Highly wear-resistant and corrosion-resistant material and centrifugal pump
By adopting a highly wear -resistant and corrosion -resistant material composed of a variety of polymer materials, the problem of easily corrosion and wear in the use of centrifugal pumps during use, and realizes the high -power performance, wear resistance and corrosion resistance of the material Improved the service life of the centrifugal pump.
Patent Information
- Application Number
- CN202310895177.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-20
AI Technical Summary
During use, centrifugal pumps are susceptible to corrosive liquids and slurries containing high concentration of solid particles, resulting in corrosion and wear, affecting service life.
A high-wear-resistant and corrosion-resistant material, which is based on PA resin, ABS resin, N-phenyl Marlayamide-styrene-Malanic anhydride-acrylamide tetramids, elastic elastic body, epoxy elasticity, The glass fiber, moltosanide, polytetrafluoroethylene, and solid fatty acid are composed of dual screw extruded machines to form materials with high mechanics and abrasion resistance and corrosion resistance, and are used to make centrifugal pumps.
This material significantly improves the abrasion resistance and corrosion resistance of the centrifugal pump, extend the service life, and shows excellent mechanical properties and wear resistance and corrosion resistance in the performance test.
Smart Images

Figure CN116715958B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a highly wear-resistant and corrosion-resistant material and a centrifugal pump. Background Art
[0002] Centrifugal pumps are a common type of fluid conveying equipment. Their main function is to transport liquid from one place to another. They are suitable for conveying rapid and large-flow liquids. The working principle of centrifugal pumps is generated by centrifugal force. Driven by the pump shaft rotor, the liquid enters from the suction port of the pump body. Under the centrifugal force of the high-speed rotating rotor, the liquid is forced to squeeze outward, forming a pressure difference with smaller and smaller diameters, and finally sending the liquid out from the outlet. Centrifugal pumps are widely used in chemical, metallurgical, mining, petroleum and other industries. They have many advantages such as strong conveying capacity, large fluid conveying volume, good stability, simple operation, and no need for manual control. However, during the use of centrifugal pumps, they will come into contact with many corrosive liquids and slurries containing high concentrations of solid particles, which will undoubtedly cause corrosion and wear of the centrifugal pumps and affect their service life. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a highly wear-resistant and corrosion-resistant material and a centrifugal pump.
[0004] The technical solutions adopted are as follows:
[0005] A highly wear-resistant and corrosion-resistant material, comprising, by weight:
[0006] 60-80 parts of PA resin, 10-30 parts of ABS resin, 5-15 parts of N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer, 1-5 parts of epoxidized elastomer, 20-40 parts of glass fiber, 10-20 parts of molybdenum disulfide, 10-20 parts of polytetrafluoroethylene, and 0.1-0.5 parts of zinc stearate.
[0007] Furthermore, the PA resin is PA 66 and / or PA 6.
[0008] Furthermore, the preparation method of the N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer is as follows:
[0009] Add xylene and free radical initiator into a reaction bottle, raise the temperature to 60-70°C under the protection of inert gas, dissolve N-phenylmaleimide, styrene, maleic anhydride and acrylamide in xylene and add dropwise into the reaction bottle under vigorous stirring. After the addition is completed, control the polymerization temperature to ≤100°C and react for 2-4h. After cooling to room temperature, add the reaction solution dropwise into methanol to produce a large amount of precipitate. Filter and dry to obtain a crude product. Slurry the crude product in methanol, filter and dry.
[0010] Furthermore, the weight ratio of N-phenylmaleimide, styrene, maleic anhydride and acrylamide is 8-15:8-15:0.5-1.5:1-3.
[0011] Furthermore, the epoxidized elastomer is any one or more combinations of POE-g-GMA, SEBS-g-GMA, and EPDM-g-GMA.
[0012] Furthermore, a nucleating agent is attached to the glass fiber.
[0013] Furthermore, the nucleating agent is nano-CaTiO3.
[0014] Furthermore, the preparation method of the glass fiber is as follows:
[0015] Add KH550 to ethanol-water solution and stir to hydrolyze it. Then add glass fiber, stir thoroughly and filter it out. Add it to nano-CaTiO3 suspension and stir for 10-30 minutes. Then filter, wash and dry it.
[0016] The present invention provides a method for preparing a highly wear-resistant and corrosion-resistant material:
[0017] PA resin, ABS resin, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer, epoxidized elastomer, molybdenum disulfide, polytetrafluoroethylene and zinc stearate are mixed evenly, put into the feeding port of a twin-screw extruder, glass fiber is added from the feeding port, and extruded through the twin-screw extruder. The extruded thin strip product is cooled, pulled, pelletized, and vibrated and sieved to obtain pellets.
[0018] Furthermore, the temperatures of the feeding section, melting section and metering section of the twin-screw extruder are 250-260° C., 270-280° C. and 290-300° C. respectively, and the screw speed is 450-480 r / min.
[0019] The present invention also provides a centrifugal pump, the component structure of which includes the above-mentioned high wear-resistant and high corrosion-resistant material.
[0020] Beneficial effects of the present invention:
[0021] The present invention provides a highly wear-resistant and highly corrosion-resistant material. PA resin has the characteristics of high strength, wear resistance, solvent resistance, self-lubrication, etc., but also has the defects of poor dimensional stability and low impact resistance. ABS resin with good dimensional stability and impact resistance is blended and modified with it to obtain a new blend having the advantages of both polymer materials. The amide group-containing N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer is used as a reactive compatibilizer to reduce the interfacial tension of the two phases, reduce the size of the dispersed phase, improve the compatibility of the blend of PA resin and ABS resin, and enhance the mechanical, heat-resistant, wear-resistant and corrosion-resistant properties of the material. The epoxidized elastomer can also reduce the size of the dispersed phase in the blend, inhibit the agglomeration of ABS resin particles, make the two phases combine more closely, and improve the phase morphology of the blend. In addition, the epoxidized elastomer The epoxy functional groups in the structure can react chemically with the amino groups and carboxyl groups on the PA resin molecular chain to form a chemical bond connection, which can improve the internal bonding strength. The nucleating agent is attached to the glass fiber by electrostatic adsorption, and the heterogeneous nucleation effect of nano-CaTiO3 is used to induce the PA resin to crystallize on the surface of the glass fiber, thereby improving the interface compatibility between the two and promoting the improvement of various performances of the material. Molybdenum disulfide and polytetrafluoroethylene are two highly efficient lubricating materials. After being added, the surface of the material is smooth, so that it has a lower friction coefficient and wear resistance. After testing, the high wear-resistant and high corrosion-resistant material prepared by the present invention has excellent mechanical properties and wear resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The cross-sectional SEM image of the sample prepared in Example 1 of the present invention shows the bonding interface between the glass fiber and the resin matrix. The glass fiber has good wettability, and a portion of the resin matrix remains on the extracted glass fiber, which is the reason why the sample has good mechanical strength. DETAILED DESCRIPTION
[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0024] Embodiment 1:
[0025] A highly wear-resistant and corrosion-resistant material, comprising, by weight:
[0026] PA 66 75 parts, ABS resin 20 parts, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer 10 parts, POE-g-GMA 2.5 parts, glass fiber 30 parts, molybdenum disulfide 15 parts, polytetrafluoroethylene 10 parts, zinc stearate 0.5 parts.
[0027] Wherein, the preparation method of N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer is as follows:
[0028] Add 200mL of xylene and 0.1g of benzoyl peroxide into a 500mL three-necked reaction flask with a stirring paddle and a thermometer, pass through it under argon protection, heat it to 70°C, and under vigorous stirring, dissolve 15g of N-phenylmaleimide, 10g of styrene, 1.5g of maleic anhydride, and 3g of acrylamide in 80mL of xylene and add them dropwise into the reaction flask. After the addition is completed, control the polymerization temperature at 95±5°C to react for 3h. After cooling to room temperature, add the reaction solution dropwise into 1.5L of methanol to produce a large amount of precipitate, filter it, and dry the obtained product at 80°C for 10h to obtain a crude product. Add the crude product into 8 times its weight of methanol, beat it at room temperature for 5h, and then filter it. Dry the obtained product at 80°C for 10h.
[0029] The preparation method of glass fiber is as follows:
[0030] Add 1g KH550 to an ethanol-water solution (composed of 20mL ethanol and 80mL water), heat to 50℃ and stir for 2h to hydrolyze it, then add 40g glass fiber, stir thoroughly at 200r / min for 2h, filter out, add to a nano-CaTiO3 suspension (composed of 10g nano-CaTiO3 powder, 590mL water), stir for 30min, filter, wash the product with water and dry it at 80℃ for 10h.
[0031] Preparation method of the above-mentioned highly wear-resistant and highly corrosion-resistant material:
[0032] PA 66, ABS resin, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer, POE-g-GMA, molybdenum disulfide, polytetrafluoroethylene and zinc stearate are mixed evenly, put into the feeding port of a twin-screw extruder, glass fiber is added from the feeding port, and extruded through the twin-screw extruder. The temperatures of the feeding section, melting section and metering section of the twin-screw extruder are 260° C., 280° C. and 295° C. respectively, and the screw speed is 450 r / min. The extruded thin strip product is cooled, pulled, pelletized, and vibrated to obtain pellets.
[0033] Embodiment 2:
[0034] The same as Example 1, except that, by weight, the following components are included:
[0035] PA 66 80 parts, ABS resin 30 parts, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer 15 parts, POE-g-GMA 5 parts, glass fiber 40 parts, molybdenum disulfide 20 parts, polytetrafluoroethylene 20 parts, zinc stearate 0.5 parts.
[0036] Embodiment 3:
[0037] The same as Example 1, except that, by weight, the following components are included:
[0038] PA 66 60 parts, ABS resin 10 parts, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer 5 parts, POE-g-GMA 1 part, glass fiber 20 parts, molybdenum disulfide 10 parts, polytetrafluoroethylene 10 parts, zinc stearate 0.1 parts.
[0039] Comparative Example 1:
[0040] The method is substantially the same as Example 1, except that the N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer is not added.
[0041] Comparative Example 2:
[0042] The method is substantially the same as Example 1, except that the N-phenylmaleimide-styrene-maleic anhydride terpolymer is used instead of the N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer.
[0043] Comparative Example 3:
[0044] The method is basically the same as Example 1, except that POE-g-GMA is not added.
[0045] Comparative Example 4:
[0046] The method is basically the same as Example 1, except that the glass fiber is directly added without being treated with KH550 and CaTiO3.
[0047] Comparative Example 5:
[0048] The method is basically the same as Example 1, except that nano-CaCO3 is used instead of nano-CaTiO3.
[0049] Comparative Example 6:
[0050] The method is basically the same as Example 1, except that nano-SiO2 is used instead of nano-CaTiO3.
[0051] Comparative Example 7:
[0052] The method is substantially the same as Example 1, except that zinc stearate is not added.
[0053] Performance Test:
[0054] The highly wear-resistant and highly corrosion-resistant materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-7 were used as samples for performance testing;
[0055] The tensile strength was tested according to GB / T1447-2005. The tensile specimen was dumbbell-shaped, the tensile rate was 10 mm / min, the gauge length was 50 mm, 5 specimens were tested for each type, and the average value was calculated in MPa.
[0056] The bending strength is tested according to GB / T9341-2008, with a test rate of 2mm / min, a span of 64mm, a length of 80mm, a width of 10mm, and a height of 4mm. Five strips of each type of specimen are tested and the average value is calculated in MPa.
[0057] Unnotched impact strength is tested according to GB / T1043.1-2008. The impact direction is parallel to the width of the sample. The support line spacing of the long sample with a length of 80mm, a width of 10mm and a height of 4mm is 62mm. Ten samples of each type are tested and the average value is calculated in kJ·m -2 ;
[0058] Wear resistance is tested according to GB / T5478-2008, with 1000g weight on each side, 5000 turns, and a rotation speed of 60r / min. For each sample, 3 discs with a thickness of 3 mm were tested and the average value was calculated.
[0059] The friction coefficient was tested according to GB / T3960-2016. The test ring speed was 200 r / min, the wear time was 2 h, the load was 196 N, 3 samples of each type were tested, and the average value was calculated in mg. The above test results are shown in Table 1.
[0060] Two 1500mL beakers were placed in a constant temperature (25°C) water bath, and 10% sodium hydroxide aqueous solution and 10% hydrochloric acid were placed in the beakers respectively. The samples prepared in Examples 1-3 and pure PA66 were placed in these two media for 10 days and then taken out. In the shortest possible time, their tensile strength, flexural strength, unnotched impact strength and wear resistance were tested, and the performance degradation rate was calculated (unit: %). The test results are shown in Table 2.
[0061] Table 1:
[0062]
[0063] It can be seen from Table 1 above that the highly wear-resistant and highly corrosion-resistant material prepared in the present invention has excellent mechanical properties and wear resistance.
[0064] Table 2:
[0065]
[0066] Note: “-” represents a decrease;
[0067] It can be seen from Table 2 above that the highly wear-resistant and highly corrosion-resistant material prepared in the present invention has excellent corrosion resistance.
[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly wear-resistant and corrosion-resistant material, characterized in that: In parts by weight, comprising: 60-80 parts of PA resin, 10-30 parts of ABS resin, 5-15 parts of N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer, 1-5 parts of epoxidized elastomer, 20-40 parts of glass fiber, 10-20 parts of molybdenum disulfide, 10-20 parts of polytetrafluoroethylene, and 0.1-0.5 parts of zinc stearate; The preparation method of the glass fiber is as follows: Add KH550 to ethanol-water solution and stir to hydrolyze it. Then add glass fiber, stir thoroughly and filter it out. Add it to nano-CaTiO3 suspension and continue stirring for 10-30 minutes. Then filter, wash and dry it.
2. The highly wear-resistant and corrosion-resistant material according to claim 1, characterized in that: The PA resin is PA 66 and / or PA6.
3. The highly wear-resistant and corrosion-resistant material according to claim 1, characterized in that: The preparation method of the N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer is as follows: Add xylene and free radical initiator into a reaction bottle, raise the temperature to 60-70°C under the protection of inert gas, dissolve N-phenylmaleimide, styrene, maleic anhydride and acrylamide in xylene and add dropwise into the reaction bottle under vigorous stirring. After the addition is completed, control the polymerization temperature to ≤100°C and react for 2-4h. After cooling to room temperature, add the reaction solution dropwise into methanol to produce a large amount of precipitate. Filter and dry to obtain a crude product. Slurry the crude product in methanol, filter again and dry.
4. The highly wear-resistant and corrosion-resistant material according to claim 3, characterized in that: The weight ratio of the N-phenylmaleimide, styrene, maleic anhydride and acrylamide is 8-15:8-15:0.5-1.5:1-3.
5. The highly wear-resistant and corrosion-resistant material according to claim 1, characterized in that: The epoxidized elastomer is any one or more combinations of POE-g-GMA, SEBS-g-GMA, and EPDM-g-GMA.
6. The highly wear-resistant and corrosion-resistant material according to claim 1, characterized in that: A nucleating agent is attached to the glass fiber.
7. The highly wear-resistant and corrosion-resistant material according to claim 6, characterized in that: The nucleating agent is nano-CaTiO3.
8. A method for preparing a highly wear-resistant and corrosion-resistant material according to any one of claims 1 to 7, characterized in that: PA resin, ABS resin, N-phenylmaleimide-styrene-maleic anhydride-acrylamide tetrapolymer, epoxidized elastomer, molybdenum disulfide, polytetrafluoroethylene and zinc stearate are mixed evenly, put into the feeding port of a twin-screw extruder, glass fiber is added from the feeding port, and extrusion is performed through the twin-screw extruder. The feeding section, melting section and metering section temperatures of the twin-screw extruder are 250-260° C., 270-280° C. and 290-300° C., respectively, and the screw speed is 450-480 r / min. The extruded thin strip product is cooled, pulled, pelletized, and vibrated and sieved to obtain pellets.
9. A centrifugal pump, characterized in that: The invention comprises the highly wear-resistant and corrosion-resistant material according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-wear-resistance nano nylon material and preparation method thereof
CN104788949A
Halogen-based flame-retardant glass fiber-reinforced polyamide resin composition, and method for preparing same
CN104854192A